1994
DOI: 10.1177/001872089403600205
|View full text |Cite
|
Sign up to set email alerts
|

A Large Database Study of the Factors Associated with Work-Induced Fatigue

Abstract: A computer survey was conducted using the records of 3705 temporary employees who reported job fatigue during their assignments; 10,000 additional employees, who did not report fatigue, were also surveyed in order to establish base rates. Low job challenge, poor-quality supervision, low job control, poor job performance, and low pay rates were associated with employees' experiencing job fatigue. Low physical demand and low information-processing demand positions were also associated with the experience of fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…There is always the possibility of an inverse relationship as well. 12 Fatigue especially may lead into a negative judgement of work conditions, instead of inappropriate work conditions leading to fatigue. A prospective study should be made to investigate the predictive power of the studied job stressors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is always the possibility of an inverse relationship as well. 12 Fatigue especially may lead into a negative judgement of work conditions, instead of inappropriate work conditions leading to fatigue. A prospective study should be made to investigate the predictive power of the studied job stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Of the reported fatigue cases, 92 per cent were associated with low-control work assignments. 12 Among more speci®c job factors, high information-processing demand assignments were far less likely to be associated with reports of job fatigue than were low information-processing assignments. Contrary to expectations, sleep deprivation had a minimal impact on fatigue.…”
mentioning
confidence: 99%
“…Driving over a prolonged period of time, as in long journeys involving motorway travel, has been found to induce tiredness (Finkleman, 1994), and lapses in attention, even to the point of falling asleep at the wheel. Given the established effects of caffeine on computerised tasks, including improved reaction time, attention and increased alertness, these effects of caffeine may also be bene®cial to performance in a monotonous driving situation.…”
Section: Introductionmentioning
confidence: 99%
“…External stimulation is defined as the stimuli perceived in daily life. On the basis of a stress model, many authors assume a positive correlation between external stimulation and fatigue [6][7][8][9][10], but empirical evidence has 510 de RIJK et al also shown that low levels of external stimulation correlate with fatigue [11][12][13]. Bensing et al [2] found empirical evidence in support of too much external stimulation (having a job and children under 6 years of age) in women and too little external stimulation (being unemployed) in men relating to fatigue.…”
Section: Introductionmentioning
confidence: 99%